2006
DOI: 10.1111/j.0023-8333.2006.00349.x
|View full text |Cite
|
Sign up to set email alerts
|

Processing Instruction and a Role for Output in Second Language Acquisition

Abstract: This study addresses the role of output in second language (L2) acquisition by comparing processing instruction (PI) to communicative output (CO) tasks. Participants included 80 English-speaking adults from six university course sections of beginning L2 Spanish, with two assigned to each treatment (PI ¼ 27; CO ¼ 28) and two others comprising a control group (n ¼ 25). Instruction lasted 7 days and targeted the anticausative clitic se. One lesson was videotaped and transcribed in each treatment group. Results on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
55
2
3

Year Published

2007
2007
2017
2017

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 108 publications
(61 citation statements)
references
References 61 publications
1
55
2
3
Order By: Relevance
“…Ever since VanPatten and Cadierno (1993) published their original study, a large body of research has mushroomed comparing PI to different kinds of PBI such as traditional instruction (TI; e.g., VanPatten & Cadierno, 1993), meaning-based output instruction (MOI; e.g., Farley, 2001), meaning-based drills instruction (MDI; e.g., Keating & Farley, 2008), communicative output (CO; e.g., Toth, 2006) and dictogloss tasks (DG; e.g., Qin, 2008;VanPatten, Inclezan, Salazar, & Farley, 2009). For instance, VanPatten and Cadierno's study (1993) investigated possible differences in the effectiveness of PI and TI on the acquisition of direct object pronouns in Spanish.…”
Section: Processing Instruction and Production-based Instructionmentioning
confidence: 99%
See 1 more Smart Citation
“…Ever since VanPatten and Cadierno (1993) published their original study, a large body of research has mushroomed comparing PI to different kinds of PBI such as traditional instruction (TI; e.g., VanPatten & Cadierno, 1993), meaning-based output instruction (MOI; e.g., Farley, 2001), meaning-based drills instruction (MDI; e.g., Keating & Farley, 2008), communicative output (CO; e.g., Toth, 2006) and dictogloss tasks (DG; e.g., Qin, 2008;VanPatten, Inclezan, Salazar, & Farley, 2009). For instance, VanPatten and Cadierno's study (1993) investigated possible differences in the effectiveness of PI and TI on the acquisition of direct object pronouns in Spanish.…”
Section: Processing Instruction and Production-based Instructionmentioning
confidence: 99%
“…Not all studies in the literature, however, have found advantages of PI compared to other instructional types; this is the case for Spanish direct object pronouns and the conditional (DeKeyser & Sokalski, 1996), Spanish direct object pronouns (Keating & Farley, 2008;Morgan-Short & Bowden, 2006;Salaberry, 1997), Japanese honorifics (Nagata, 1998), French causative instruction (Allen, 2000), French direct object pronouns (Erlam, 2003), Spanish anticausative clitic se (Toth, 2006), and English present subjunctive (Farley & Aslan, 2012). All these studies, contrary to earlier PI studies, found that on the interpretation task, either the PBI and PI groups scored equally, or PBI performed better than PI; additionally, on the production task, the PBI group performed much better than PI.…”
Section: Processing Instruction and Production-based Instructionmentioning
confidence: 99%
“…The findings of the study done by Erlam et al (2009) revealed that both instructional groups significantly outperformed the control group that did not receive any instruction. Toth (2006) investigated the role of input and output in second language acquisition of Spanish morphosyntax and the results showed that both groups improved equally on a grammar task, but the output group performed better than its counterpart in a task of controlled production.…”
Section: H Related Empirical Studies On Input-based and Out-put Basementioning
confidence: 99%
“…An ongoing issue in LA is, however, how best to stimulate and channel LA. To inform this debate, more research which contrasts the learning effects of different approaches, such as Toth (2006) and Lee (2007), would be particularly useful.…”
Section: Explicit and Implicit Knowledge And Learningmentioning
confidence: 99%